Development of fuzzy navigation and instrumentation system for telediagnostic mobile robot - Vigneswaran Ramu (2012)
The absence of a specialist may lead to misdiagnosis and cause danger to the patient's life. This is one of the main concerns in most countries where there are insufficient medical specialists especially in rural area. To address this, a cost effective telediagnostic mobile robot that provides tele-presence capability for the specialist to virtually meet the patient and perform diagnosis is developed. This research highlights the development of a remote mobile robot navigation and instrumentation system as part of the telediagnostic mobile robot navigation control system and on-board medical instrument interface. It enables a user located in a different place to control the mobile robot's navigation remotely from the feedback data received from the robot. The navigation system incorporates a four wheel holonomic drive system which provides good agility to the robot. Combinations of sensors are place around the robot to provide data on the robot's surrounding during operation. The robot is fitted with safety features which include Danger Monitoring System (DMS) and Fail Safe and Auto Recovery System (FSARS). This is realized by equipping it with fuzzy logic based system to process the data and decide preventative measures to avoid danger. On the other hand, the robot's instrumentation includes a system to acquire Liquid Crystal Display (LCD) reading from a set of medical instruments using Optical Character Recognition (OCR) method on LabVIEW 2009 platform. The system is tested by a set of experiments and found to be demonstrating an acceptable performance. This system proved to be suitable for the telediagnostic mobile robot.